2005
DOI: 10.1175/bams-86-2-257
|View full text |Cite
|
Sign up to set email alerts
|

Regional Climate Model Intercomparison Project for Asia

Abstract: Phase one of the Regional Climate Model Intercomparison Project for Asia reveals the capacities of regional climate models (RCMs) for simulating the Asian monsoon climate and extreme events as well. (Mearns et al. 2001;Giorgi et al. 2001). At present, analysis of the coupled atmosphere-ocean GCM (AOGCM) simulations indicates that average biases at regional scales, when simulating present-day climate, are highly variable from region to region and across models. For example, Giorgi and Francisco (2000) find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 261 publications
(175 citation statements)
references
References 35 publications
5
169
0
1
Order By: Relevance
“…In Asia, the Regional Climate Model Intercomparison Project (RMIP; Fu et al 2005) was established to build on the developments in Europe and North America with similar goals, but with a different geographical focus than PRUDENCE and NARCCAP and with quite different climatological drivers. These included, for example, the Asian monsoon and the subcontinent (i.e., the Tibetan Plateau) downwind of the large-scale flows crossing the Eurasian continent.…”
Section: Multi-model Ensemble Projectsmentioning
confidence: 99%
“…In Asia, the Regional Climate Model Intercomparison Project (RMIP; Fu et al 2005) was established to build on the developments in Europe and North America with similar goals, but with a different geographical focus than PRUDENCE and NARCCAP and with quite different climatological drivers. These included, for example, the Asian monsoon and the subcontinent (i.e., the Tibetan Plateau) downwind of the large-scale flows crossing the Eurasian continent.…”
Section: Multi-model Ensemble Projectsmentioning
confidence: 99%
“…In order to quantify possible causes of deficiency in downscaling generated by RCM-derived errors, it is useful to adopt reanalysis data as boundary forcing, which is referred to as a perfect boundary experiment (or type 2 experiment in Castro et al 2005). There are many studies evaluating the value added by dynamical downscaling with the perfect boundary experiment (e.g., Castro et al 2005;Fu et al 2005;Xue et al 2007;Gao et al 2011). In addition to errors due to the quality of lateral boundary condition data (e.g., Gong and Wang 2000;Xue et al 2012), known sources of uncertainty generated through RCM experiments are horizontal resolution (e.g., Christensen et al 1998;Mo et al 2000;Wang et al 2003;Zhang et al 2003;Castro et al 2005;Xue et al 2007;Sato et al 2008), domain size and location (e.g., Treadon and Petersen 1993;Xue et al 2007;Gao et al 2011), lateral boundary settings (Denis et al 2003;Giorgi and Mearns 1999;Warner et al 1997), and physics schemes Liang et al 2004;Wang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Kang and Hong (2008) investigated the sensitivity of simulated climatology to convective parameterizations. Fu et al (2005) conducted the RCM inter-comparison project (RMIP), in which nine RCMs participated, and found that cumulus parameterization is the most important factor that causes diversity of simulated regional climate in East Asia. Ishizaki et al (2012) examined the RCM's ability to simulate the Japanese climate using five RCMs.…”
Section: Introductionmentioning
confidence: 99%
“…The regional climate model RIEMS has been designed within the framework of general monsoon systems (Fu 1995) since 2000 (Fu et al 2000). RIEMS has shown good performance in simulating temperature, precipitation and atmospheric circulation in the Regional Climate Model Intercomparison Project for Asia (Fu et al 2005). The present version 2.0 of RIEMS developed since 2007 with non-hydrostatic dynamics Zhao 2013) is used here to couple the land surface model (LSM) of AVIM.…”
Section: Model and Datamentioning
confidence: 99%